#### Answer

{-33}

#### Work Step by Step

5x - 4(x + 9) = 2x - 3
Step 1 : Use distributive property
5x - 4.x -4.9 = 2x - 3
x - 36 = 2x - 3
Step 2 : Collect variable terms on one side and constants on the other side.
subtract 2x from both the sides
x - 36 - 2x = 2x - 3 - 2x
-x - 36 = -3
Add 36 on both the sides
-x - 36 + 36 = -3 + 36
x = -33
Now we check the proposed solution, -33 , by replacing x with -33 in the original equation.
Step 1: the original equation 5x - 4(x + 9) = 2x - 3
Step2: Substitute -33 for x
5.(-33) - 4(-33 +9) = 2(-33) -3
Step 3: Simplify
5.(-33) - 4(-24) = 2(-33) -3
Multiply 5.(-33) = -165, 2.(-33) = -66, 4(-24) = -96
-165 + 96 = -66 -3
Solve
- 69 = -69
Since the check results in true statement, we conclude that the solution set of the given equation is {-33}